Polycultural education and its problems in the context of Russian cross-cultural contacts with asian pacific region - А. V. Alepko (Высшее образование в России, 2022)
The author analyzes the problems of polycultural education in Russian Far East region through the prism of a strong geo-political influence of Asian Pacific countries. The main vector of regional polycultural education is training for culturologists as specialists in the sphere of cross-cultural communication.